왜 못난이 농산물로 만든 건조과일이 일반 건조과일과 비슷한 가치를 갖는가? - 김지열; 이철 (식품과학과 산업, 2023)
This study investigates why consumers value upcycled dried fruit from ugly produce similarly to that from regular produce. Three main reasons emerged: 1) Processing reduces appearance differences, leading to homogenization and diminished quality differences; 2) Packaging design grants ugly produce products a unique market position; 3) Consumers consider positive impacts on the environment, food waste reduction, and support for domestic farmers. However, concerns may arise about potential price increases and disruption to the regular produce market if the ugly produce market grows excessively.
Keywords: ugly produce; ugly fruit; homogenization; packaging; meaning-out